PENERAPAN METODE INFILTRATION DITCH SEBAGAI USAHA PENURAPAN AIR TANAH UNTUK SUPLAY AIR BERSIH BAGI MASYARAKAT DESA WANGA - Nirmalawati, Nirmalawati (MEKTEK, 2010)
Wanga village, according to geoelectric measurements, has groundwater at depths of > 34 meters such thatit was detected below the surface, and rainfall of 3165 mm/year. This condition makes the groundwaterrecharge area is so big, and will be very potential. But in fact during the dry season, the surface water is notsufficient. The purpose of this research is to assist residents in the village Wanga in providing clean waterusing the application of the method